2020
DOI: 10.1186/s12884-020-03326-8
|View full text |Cite
|
Sign up to set email alerts
|

Iron stores in pregnant women with sickle cell disease: a systematic review

Abstract: Background Gradual improvements in the management of sickle cell disease (SCD), have led to an increase in the number of women with SCD who reach the age of procreation. However, evidence on the iron status of pregnant women with sickle cell disease (PWSCD) remains inconclusive. We conducted the first systematic review on the prevalence, determinants and maternal/foetal outcomes of iron deficiency anaemia among PWSCD. Methods We searched MEDLINE, EMBASE, Global Health, Africa Index Medicus, the Cochrane libr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Aroke et al reported an extremely variable prevalence of iron-deficiency anemia during pregnancy among SCD patients, ranging from 6.7% to 83.3%, using multiple diagnostic tools (bone-marrow iron staining, serum iron levels, and/or ferritin levels) [132]. As SCD is responsible for intravascular hemolysis, SCD patients have lower concentrations of haptoglobin (0.09 versus 1.18 g/L, p < 0.0001) and hemopexin (0.42 versus 1.05 g/L, p = 0.0001) than unaffected controls [AG Cordier and K Peoc'h, Personal communication].…”
Section: Sickle-cell Diseasementioning
confidence: 99%
“…Aroke et al reported an extremely variable prevalence of iron-deficiency anemia during pregnancy among SCD patients, ranging from 6.7% to 83.3%, using multiple diagnostic tools (bone-marrow iron staining, serum iron levels, and/or ferritin levels) [132]. As SCD is responsible for intravascular hemolysis, SCD patients have lower concentrations of haptoglobin (0.09 versus 1.18 g/L, p < 0.0001) and hemopexin (0.42 versus 1.05 g/L, p = 0.0001) than unaffected controls [AG Cordier and K Peoc'h, Personal communication].…”
Section: Sickle-cell Diseasementioning
confidence: 99%
“…women, and children aged 6-24 months are usually the group most affected by iron deficiency (Agegnehu et al, 2019). Iron deficiency anemia in pregnant women is known to reach 38.2% on a global scale (Aroke et al, 2020). The number of cases of anemia has been increasing lately from 37.10% (2013) to 48.…”
mentioning
confidence: 99%